The structure and significance of Nothern Sotho traditional songs with specific reference to children. - Mabitsela, Ablonia Dihloriso (My University, 2005)
The study aims at analysing the structure and significance of Northern Sotho traditional songs with reference to children. This will be achieved by analysing the internal and external structures of traditional songs using poetic devices. The study will also show the benefits (significances) children get from those songs. It was discovered that most of the songs are affected by the introduction of foreign cultures and languages in the communities and they are sung in many different languages. The study recommends that Northern Sotho children’s traditional songs be included in the school curriculum in all grades at both primary and secondary schools.
Thesis (M.A.) (African Languages) --University of Limpopo, 2005.
Keywords: Northern Sotho songs